New water mites of the family Hygrobatidae (Acari, Hydrachnidia) from Turkey - Esen, Yunus; Pesic, Vladimir; Erman, Orhan; Kaya, Yucel (Pensoft Publishers, 2013)
In this study, the findings of three water mite species of the family Hygrobatidae collected from different streams in Turkey were evaluated. Hygrobates (s. str.) anatolicus Esen & Pesic, sp. n. is described as new for science. Hygrobates (Rivobates) diversiporus Sokolow, 1927 and Atractides (s. str.) nikooae Pesic, 2004, which were illustrated and thoroughly discussed, are new records for the Turkish fauna.
Keywords: Acari; Hygrobatidae; water mites; new records; Turkey